1986
DOI: 10.1002/j.1556-6978.1986.tb00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Feminist Counseling Skills: An Evaluation

Abstract: Feminist counseling was analyzed into four core skills: social analysis, androgyny encouragement, self-disclosure, and behavior feedback. A 5-week feminist skill-training program was developed for 45 counselors divided into two groups, matched on years of counseling experience and scores on Spence and Helmreich's Attitude Toward Women Scale (AWS). Training of the second group was delayed for 5 weeks to provide a control for the training of the first group. Participants' attitudes and skill levels before, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The extent to which they are doing so is not known, however, nor is it clear what models they favor. Teaching about gender issues has received scant attention in the counselor education literature (e.g., Cook, Warnke, & Dupuy, 1993: Russell, 1986: Van Buren, 1992. Insight into current teaching practices on gender issues can help to gulde counselor educators in addressing CACREP recommendations pertaining to gender in their own programs.…”
mentioning
confidence: 99%
“…The extent to which they are doing so is not known, however, nor is it clear what models they favor. Teaching about gender issues has received scant attention in the counselor education literature (e.g., Cook, Warnke, & Dupuy, 1993: Russell, 1986: Van Buren, 1992. Insight into current teaching practices on gender issues can help to gulde counselor educators in addressing CACREP recommendations pertaining to gender in their own programs.…”
mentioning
confidence: 99%
“…Some research has examined the variable of self-disclosure as it relates specifically to feminist therapy. Evaluating the effectiveness of training persons in feminist-therapy techniques, Russell (1986) examined trainee outcome after a program in feminist microcounseling skills, including self-lsclosure. Trainees completed a 5-week feminist skill-training program using counseling simulations.…”
Section: Research On Self-disclosure In Feminist Therapymentioning
confidence: 99%
“…This effect had &minished during the follow-up period, however. Russell (1986) suggested that the selfdisclosure skill is likely a part of the repertoire of most counselors and that training temporarily augments skill prevalence.…”
Section: Research On Self-disclosure In Feminist Therapymentioning
confidence: 99%
See 2 more Smart Citations